The Effectiveness of Educational Media on Patients' Clean and Healthy Living Behavior (PHBS) in Handwashing at the Outpatient Department of Annisa General Hospital, Citeureup, in 2025 - Devia Lydia Putri; Ifania Ifania; Ida Nuraida; Winda Dwi Lestari; Atri Mulyani; Gisma Maldini (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Hospitals are health care facilities that not only serve to cure diseases but also play a crucial role in disease prevention and health promotion. Clean and healthy living behavior refers to conscious health practices undertaken by individuals, families, groups, or communities to improve overall health quality and prevent illness (Ministry of Health of the Republic of Indonesia, 2023). An initial survey conducted by researchers at Annisa General Hospital, Citeureup, on June 17, 2025, revealed that among 12 respondents in the outpatient department, 8 individuals (66.7%) had never received direct education on clean and healthy living behavior related to handwashing, while only 4 individuals (33.3%) had received such education. Methods: This study employed a pre-experimental design using a one-group pretest-posttest model. The study population consisted of 5,010 patients, and the sample included 38 participants. Data were analyzed using univariate analysis (frequencies) and bivariate analysis with the Wilcoxon Signed-Rank Test. Results: Based on Table 4.1, a total of 38 participants were included. Before the intervention, 18 individuals (47.4%) were categorized as having insufficient knowledge. Following the intervention, a significant improvement was observed, with only 1 participant (2.6%) remaining in the insufficient knowledge category. Twenty-eight participants (73.7%) were over the age of 35, 25 (65.8%) were unemployed, and 2 (5.3%) had never attended school. According to Table 4.4, the Z-score was -5.108, with a significance level (Asympt. Sig. 2-tailed) of 0.000. Conclusion: Participants’ understanding improved after receiving instructions through a poster illustrating the six steps of proper handwashing with soap. The Wilcoxon Signed-Rank Test indicated that no participants experienced a decrease in their scores. A total of 89.5% of participants showed improved scores after viewing the poster. These findings demonstrate that visual poster-based education is effective in improving general understanding of proper handwashing practices.